HUBUNGAN PERAN GURU TERHADAP PENGETAHUAN REMAJA TENTANG SEKS BEBAS - Ambia Nurdin (Jurnal Dedikasi Pendidikan, 2017)
Some factors supporting occur sex behavior among teenagers, among others; environmental factors, the electronic media, the lack of information and lack of religious education. The school environment has contributed to the occurrence of free sex. Schools are less disciplined and ignored kaedah-kaedah religion, often no lessons during school hours. The aim of research to identify the role of teachers' relationship to knowledge about adolescent promiscuity. This study is a parallel analytic design with cross sectional study to identify the relationship of the teacher's role pengatahuan teens about sex include the variable role of teachers as educators and counselors and knowledge of adolescents about sex. This research was conducted in SMA Negeri 1 Indrapuri subdistrict, Aceh Besar district. Sampling was done by stratified random sampling with the number of respondents 82 people. This research was conducted in SMA Negeri 1 Indrapuri subdistrict, Aceh Besar District by distributing questionnaires. Univariate and bivariate data analysis using a computer program. The results showed no significant correlation between the teacher's role as a teacher and mentor teens about sex in which the test results obtained by statistical P-value = 0.006 where the result is less than the value of α = 0.05. Knowledge of adolescents about sex is strongly influenced by the role of a good teacher. Expected in educational institutions SMA N 1 Subdistrict Indrapuri to play well in fostering the students and teach them about sex.